Efficient Snell’s law solution for generating robust acoustic tweezers in dual-layered media - Pham, Huy Q.; Nguyen, Nhung; Tran, Quang; Le, Trung B.; Le, Trung Q. (Frontiers in Acoustics, 2024)
Acoustic tweezers can trap and manipulate a target along a desired path without physical contact. Potential applications of this technology may require the propagation of acoustic waves through nonhomogeneous media. It is typically assumed that the acoustic impedance of media is the same. However, this assumption leads to reduced efficiency in both the trapping accuracy and strength of the acoustic tweezers. In this study, we propose a method to derive phases driving an 8x8 array of ultrasonic transducers using generalized Snell's law to account for the variation in the speed of sound between media layers of planar or non-planar interfaces. The results indicate that the tweezers formed with our approach maintain their patterns and trapping capability at selected trapping locations. In addition, our method significantly enhances the trapping precision and force, achieving up to ten times greater force and more accurate alignment with the selected trapping points compared to previous methods that assume a uniform speed of sound.